Molecular biology of the cell: an introduction to the molecular biology of the cell / Alberts Bray...[el at.] - Bray, AlbertsAuthor
"For nearly a quarter century Molecular Biology of the Cell has been the leading cell biology textbook. This tradition continues with the new Fifth Edition, which has been completely revised and updated to describe our current, rapidly advancing understanding of cell biology. To list but a few examples, a large amount of new material is presented on epigenetics; stem cells; RNAi; comparative genomics; the latest